2021
DOI: 10.3390/healthcare9111407
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and COVID-19: Empowering Standards of Management for Patients Affected by Phenylketonuria and Hyperphenylalaninemia

Abstract: Phenylketonuria (PKU) and Hyperphenylalaninemia (HPA) are inborn errors of metabolism (IEM) due to mutations in the PAH gene resulting in increased blood phenylalanine (Phe) concentrations. Depending on the Phe levels, a lifelong dietary intervention may be needed. During the COVID-19 pandemic, finding new strategies to ensure follow-up and metabolic control for such patients became mandatory and telehealth was identified as the most eligible tool to provide care and assistance beyond barriers. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Data on patients affected by PKU in Italy collected retrospectively from April 2019 to March 2021 demonstrated that telehealth seemed to be a useful tool to improve the adherence to treatment, it was more effective in reaching patients who made great effort to adhere to the clinic’s face-to-face appointments (such as the working patients) and guaranteed continuous assistance and care during the pandemic. Moreover, PKU patients expressed great satisfaction with the telemedicine offered services [ 15 ]. Data collected by surveys showed that caregivers of PKU pediatric patients in Poland reported better therapy compliance, more frequent contacts with specialists during the six-week pandemic period (Summer 2020) and more satisfaction with remote visits than adult patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on patients affected by PKU in Italy collected retrospectively from April 2019 to March 2021 demonstrated that telehealth seemed to be a useful tool to improve the adherence to treatment, it was more effective in reaching patients who made great effort to adhere to the clinic’s face-to-face appointments (such as the working patients) and guaranteed continuous assistance and care during the pandemic. Moreover, PKU patients expressed great satisfaction with the telemedicine offered services [ 15 ]. Data collected by surveys showed that caregivers of PKU pediatric patients in Poland reported better therapy compliance, more frequent contacts with specialists during the six-week pandemic period (Summer 2020) and more satisfaction with remote visits than adult patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like other remote medical assistance strategies which had a positive impact on IEMs patients during the pandemic [34,35], the program guaranteed continuous dietary supervision of our patients throughout lockdown periods, and allowed us to remotely implement emergency dietary adaptations in cases of acute illnesses. Odimet traffic analysis in the 5-year study period confirms the growing use of this tool.…”
Section: Discussionmentioning
confidence: 99%
“…The early detection of HPA and its treatment can prevent neurological damags [24][25][26][27][28][29] . The patients are referred to the specialized metabolic centers in different ways.…”
Section: The Pku Optimized Patient Care Pathwaymentioning
confidence: 99%
“…Finally, the organization of biochemical laboratory tests (blood Phe measurements) should be mandatory. The primary goal of treatment is normal neurocognitive and psychosocial functioning [24][25][26][27][28][29] . PKU treatment consists of dietary management: natural protein restriction, Phe-free/low phenylalanine protein in substitutes, and low protein (LP) special food.…”
Section: The Pku Optimized Patient Care Pathwaymentioning
confidence: 99%